2007
DOI: 10.1682/jrrd.2007.02.0032
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive enhancement therapy with work therapy in schizophrenia: 6-month follow-up of neuropsychological performance

Abstract: Abstract-Cognitive deficits are a major determinant of social and occupational dysfunction in schizophrenia, and new treatments are needed that address these impairments. The current study determined whether neurocognitive enhancement therapy (NET) in combination with work therapy (WT) would show improvement in performance on neuropsychological tests that endured 6 months after completion of training. A total of 145 participants with schizophrenia or schizoaffective disorder were randomly assigned to NET + WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 34 publications
3
103
1
7
Order By: Relevance
“…In recent years different integrated interventions have been developed, targeting both cognitive and psychosocial deficits (Bell et al 2001;Hogarty et al 2004;Galderisi et al 2010;Lindenmayer et al 2013;Medalia & Saperstein, 2013). Although still heterogeneous, results mainly show that combined rehabilitation programmes have a greater impact than single interventions on functional outcome, suggesting that social cognitive rehabilitation programmes in schizophrenia should also include neurocognitive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years different integrated interventions have been developed, targeting both cognitive and psychosocial deficits (Bell et al 2001;Hogarty et al 2004;Galderisi et al 2010;Lindenmayer et al 2013;Medalia & Saperstein, 2013). Although still heterogeneous, results mainly show that combined rehabilitation programmes have a greater impact than single interventions on functional outcome, suggesting that social cognitive rehabilitation programmes in schizophrenia should also include neurocognitive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…18 In this study, in K-MMSE total score, the experimental group showed statistically meaningful improvements compared to the control group, and between the sub-items, a statisti- CNT was performed for the subacute stroke patients with accompanying cognitive impairments.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, the studies presented here have been selected on the basis that they employ assessment tasks that are different from tasks used during training. Several randomized controlled trials have been conducted to evaluate the effectiveness of CACR in schizophrenia (Bell et al, 2001;Bellucci et al, 2002;Burda et al, 1994;Field et al, 1997;Greig et al, 2007;Hogarty et al, 2004;Kurtz et al, 2007;Medalia et al, 2000;Medalia et al, 2001;Sartory et al, 2005;Vauth et al, 2005). Most have reported improvements of cognitive performances, with some exceptions as for example Field and colleagues (1997) and Medalia and colleagues (2000).…”
Section: Clinical Evaluationsmentioning
confidence: 99%
“…Most have reported improvements of cognitive performances, with some exceptions as for example Field and colleagues (1997) and Medalia and colleagues (2000). Studies report improvements in various cognitive domains such as: speed of processing (Bellucci et al, 2002;Burda et al, 1994;Hogarty et al, 2004;Kurtz et al, 2007;Sartory et al, 2005), attention (Vauth et al, 2005), working memory (Bell et al, 2001;Burda et al, 1994;Hogarty et al, 2004;Kurtz et al, 2007), verbal memory (Bellucci et al, 2002;Burda et al, 1994;Hogarty et al, 2004;Kurtz et al, 2007;Sartory et al, 2005;Vauth et al, 2005), visual memory (Kurtz et al, 2006), reasoning and problem solving (Bell et al, 2001;Hogarty et al, 2004;Kurtz et al, 2007;Medalia et al, 2001) and social cognition (Bell et al, 2001;Hogarty et al, 2004). Bellucci and colleagues (2002) investigated the effect of CACR on symptoms.…”
Section: Clinical Evaluationsmentioning
confidence: 99%